Impaired mitochondrial function due to familial Alzheimer's disease-causing presenilins mutants via Ca2+ disruptions. Issue 5 (May 2016) - Toglia, Patrick; Cheung, King-Ho; Mak, Don-On Daniel; Ullah, Ghanim
Abstract : Graphical abstract: Abstract : Highlights: FAD causing PS mutants cause enhanced Ca 2+ release resulting in impaired mitochondrial function. Exaggerated Ca 2+ absorption depolarizes mitochondrial membrane potential, reducing proton pumping. ATP production decreases in cells expressing FAD causing PS-mutants. ROS production increases in FAD causing PS-mutant cells due to enhanced oxygen consumption. Abstract: Mutants in presenilins (PS1 or PS2) is the major cause of familial Alzheimer's disease (FAD). FAD causing PS mutants affect intracellular Ca 2+ homeostasis by enhancing the gating of inositol trisphosphate (IP3 ) receptor (IP3 R) Ca 2+ release channel on the endoplasmic reticulum, leading to exaggerated Ca 2+ release into the cytoplasm. Using experimental IP3 R-mediated Ca 2+ release data, in conjunction with a computational model of cell bioenergetics, we explore how the differences in mitochondrial Ca 2+ uptake in control cells and cells expressing FAD-causing PS mutants affect key variables such as ATP, reactive oxygen species (ROS), NADH, and mitochondrial Ca 2+ . We find that as a result of exaggerated cytosolic Ca 2+ in FAD-causing mutant PS-expressing cells, the rate of oxygen consumption increases dramatically and overcomes the Ca 2+ dependent enzymes that stimulate NADH production. This leads to decreased rates in proton pumping due to diminished membrane potential along with less ATP and enhanced ROS production. These results show that through Ca 2+ signaling disruption, mutant PS leads to mitochondrial dysfunction and potentially to cell death.